Tunda Pilkada: Apakah Advokasi Digital Berhasil Memengaruhi Proses Pembuatan Kebijakan? - Firda Aulia; Bevaola Kusumasari (Program Studi Ilmu Komunikasi, 2022)
Digital advocacy is a growing and interesting area of research. This study aims to analyze the actors, processes, and effectiveness of digital advocacy regarding the postponement of the local elections in Indonesia in 2020 carried out by collective action using Twitter hashtags. Data in this study is the tweet related to the hashtag “Tunda Pilkada” from March 15 to December 8, 2020. The author argues that despite social media facilitating advocacy, not all digital advocacies provide effectiveness in influencing public policy. This study uses mixed research methods by combining a social network analysis approach to identify the actors. Hence, this study uses a qualitative content analysis approach to analyze social media-based advocacy models and identify failures in digital advocacy. The research findings found that individuals, not advocacy groups drove collective action. Furthermore, research also proves that hashtags are effective in reaching, building connections in public, and mobilizing. Finally, this study found that the failure of digital advocacy was caused by various factors that came from internal and external collective action. Our research contributes to the development of studies on digital advocacy.